A case study on TBM cutterhead temperature monitoring and mud cake formation discrimination method - Jie Fu (Nature Portfolio, 2021)
Abstract The mud cake is easily formed during the tunnel boring machine (TBM) excavation in clay soils or rocks containing clay minerals. Mud cake will lead to soil disturbance of tunnel face, clogging cutterhead and even affect the construction efficiency and personnel safety. In this study, a discrimination method of mud cake formation based on cutterhead temperature was proposed. An online monitoring system was designed and installed on the slurry balance TBM. The results show that: (a) the cutterhead temperature data can be reliably detected and transmitted by the system; (b) in a tunneling cycle, the temperature at some positions of the cutterhead will increase first and then decrease; (c) during the field test, the temperature variation is around 2.5 °C under the normal condition, but the temperature variation will increase more than 50 °C due to the mud cake or geological change; (d) compared with the cooling rate, mud cake formation can be accurately discriminated.